Designated ligand functionalization of gold nanoparticles for optimizing blue-phase liquid crystal composites - Orzechowski, Kamil; Wasiluk, Martyna; Jabłoński, Konrad; Milewska, Weronika; Strzeżysz, Olga; Wang, Chun-Ta; Lewandowski, Wiktor; Woliński, Tomasz (Photonics Letters of Poland, 2024)
This work presents the impact of the composition of the organic shell of 4 nm gold nanoparticles (Au NPs) on the optical properties and stability of the nanoparticle-doped blue-phase liquid crystals (BPLCs). Particularly, we show that the binary shell of NPs, comprising LC-like ligands, can significantly enhance the thermal stability of BPs. Moreover, modifying the shell composition enables control over the Bragg wavelength of BPLCs. Our findings highlight the potential of ligand-functionalized Au NPs to optimize BPLC-based photonic devices, emphasizing ligand functionalization as a crucial factor for improving stability of NPs, and controlling BPLC properties. Full Text: PDF References S. Meiboom and M. Sammon, "Structure of the Blue Phase of a Cholesteric Liquid Crystal", Phys. Rev. Lett., 44(13), 882 (1980). CrossRef S. Tanaka et al. "Muographic mapping of the subsurface density structures in Miura, Boso and Izu peninsulas, Japan", Sci. Rep. 5(1), 16180 (2015). CrossRef W. Cao, A. Muñoz, P. Palffy-Muhoray, B. Taheri, "Lasing in a three-dimensional photonic crystal of the liquid crystal blue phase II", Nat. Mater. 1(2), 111 (2002). CrossRef H. Yoshida et al. "Heavy meson spectroscopy under strong magnetic field", Phys. Rev. E 94(4), 042703 (2016). CrossRef K. Orzechowski et al. "Polarization properties of cubic blue phases of a cholesteric liquid crystal", Opt. Mater. 69, 259 (2017). CrossRef H. Yoshida et al. "Nanoparticle-Stabilized Cholesteric Blue Phases", Appl. Phys. Express 2(12), 121501 (2009). CrossRef M. A. Gharbi et al. "Reversible Nanoparticle Cubic Lattices in Blue Phase Liquid Crystals", ACS Nano, 10(3), 3410 (2016). CrossRef W.-L. He et al. "Preparation and optical properties of Fe3O4 nanoparticles-doped blue phase liquid crystal", hys. Chem. Chem. Phys. 18(42), 29028 (2016). CrossRef A.P. Draude, T.Y. Kalavalapalli, M. Iliut, B. McConnell, and I. Dierking, "Stabilization of liquid crystal blue phases by carbon nanoparticles of varying dimensionality", Nanoscale Adv. 2(6), 2404 (2020). CrossRef M. Lavrič et al. "Blue phase stabilization by CoPt-decorated reduced-graphene oxide nanosheets dispersed in a chiral liquid crystal", J. Appl. Phys. 127(9), 095101 (2020). CrossRef M. Ravnik, G.P. Alexander, J.M. Yeomans, and S. Žumer, "Three-dimensional colloidal crystals in liquid crystalline blue phases", Proc. Natl. Acad. Sci. 108(13), 5188 (2011). CrossRef K. Orzechowski et al. "Achiral Nanoparticle-Enhanced Chiral Twist and Thermal Stability of Blue Phase Liquid Crystals", ACS Nano 16(12), 20577 (2022). CrossRef U.N. Tohgha, E.P. Crenshaw, M.E. McConney, K.M. Lee, N.P. Godman, "Tuning of optical properties and phase behavior of Nanomaterial-stabilized blue phase liquid crystals", J. Colloid Interface Sci. 639, 401 (2023). CrossRef O. Chojnowska, R. Dąbrowski, J. Yan, Y. Chen, S.T. Wu, "Electro-optical properties of photochemically stable polymer-stabilized blue-phase material", J. Appl. Phys. 116(21), 213505 (2014). CrossRef P. Kula, J. Herman, O. Chojnowska, "Synthesis and properties of terphenyl- and quaterphenyl-based chiral diesters", Liq. Cryst. 40(1), 83 (2013). CrossRef M. Brust, M. Walker, D. Bethell, D.J. Schiffrin, R. Whyman, "Synthesis of thiol-derivatised gold nanoparticles in a two-phase Liquid–Liquid system", J. Chem. Soc. Chem. Commun. 7, 801 (1994). CrossRef J. Grzelak, M. Żuk, M. Tupikowska, and W. Lewandowski, "Modifying Thermal Switchability of Liquid Crystalline Nanoparticles by Alkyl Ligands Variation", Nanomaterials 8(3), 147 (2018). CrossRef M. Bagiński et al. "Understanding and Controlling the Crystallization Process in Reconfigurable Plasmonic Superlattices", ACS Nano 15(3), 4916 (2021). CrossRef